2011
DOI: 10.1097/sla.0b013e3182369128
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Upper, Middle, and Lower Third Mucosal or Submucosal Infiltration in Early Esophageal Cancer

Abstract: After esophagectomy, the prognosis of patients with sm1/sm2 infiltration is as good as for patients with mucosal carcinoma. Sm3 infiltration is the worst prognostic factor in pT1 esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(69 citation statements)
references
References 39 publications
4
61
2
2
Order By: Relevance
“…In case of only incipient submucosal invasion (pT1b sm1), the risk of LN metastasis ranges from 0 to 20 % [21][22][23][24][26][27][28][29][30][31]. Moreover, two retrospective surgical series suggested that among the sm1 EAC lesions, there might be a favorable histological pattern going along with a very low risk of LN metastasis [21,22], in accordance with rates known from pT1a EAC [19,[21][22][23][24].…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…In case of only incipient submucosal invasion (pT1b sm1), the risk of LN metastasis ranges from 0 to 20 % [21][22][23][24][26][27][28][29][30][31]. Moreover, two retrospective surgical series suggested that among the sm1 EAC lesions, there might be a favorable histological pattern going along with a very low risk of LN metastasis [21,22], in accordance with rates known from pT1a EAC [19,[21][22][23][24].…”
mentioning
confidence: 71%
“…Patients with ulcerated neoplasia are, in general, not eligible for an ET approach. It is important to point out that the macroscopic tumor type, including ulcerated lesions, may be difficult to assess during a retrospective surgical study [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rate der Lymphknotenmetastasen deutlich an, sodass die chirurgische Resektion mit Lymphadenektomie gefordert werden muss [8,10]. Bei pT1-sm3-Karzinomen ist sogar aufgrund der gleichen Prognose wie bei pT2 die neoadjuvante Therapie zu erwägen [8].…”
Section: Neoadjuvante Therapieunclassified
“…Bei pT1-sm3-Karzinomen ist sogar aufgrund der gleichen Prognose wie bei pT2 die neoadjuvante Therapie zu erwägen [8].…”
Section: Neoadjuvante Therapieunclassified